Sources of error in digital forensics - Horsman, Graeme (Elsevier, 2024)
The occurrence of errors in forensic practice is inevitable, and whilst we may not feel comfortable with the idea, the truth of it must be acknowledged. At a time where forensic science is under intense scrutiny regarding the quality of its work, there has never been a greater need for it. In relation to the field of digital forensics (DF), the support it offers law enforcement is fundamental to many of its inquiries, and ensuring the reliability and accuracy of its services is vital. Errors in forensic practice can have far-reaching consequences for all those involved in an investigation, and practitioners and their organisations must take steps to identify, mitigate and manage them. This work focuses on the concept of error in relation to the field of DF. It first explores what an error is and the language used to describe one before mapping potential sources of error against the stages of the DF investigative process. This is done to assist those in the DF field to identify error sources, what they are and where they come from, and to facilitate the attribution of errors to a source, helping them to address them effectively.
Keywords: Digital forensics; Error; Digital evidence; Quality assurance; Investigative process